'Printability' of Candidate Biomaterials for Extrusion Based 3D Printing: State‐of‐the‐Art. Issue 16 (30th May 2017) - Kyle, Stuart; Jessop, Zita M.; Al‐Sabah, Ayesha; Whitaker, Iain S.
Abstract : Regenerative medicine has been highlighted as one of the UK's 8 'Great Technologies' with the potential to revolutionize patient care in the 21st Century. Over the last decade, the concept of '3D bioprinting' has emerged, which allows the precise deposition of cell laden bioinks with the aim of engineering complex, functional tissues. For 3D printing to be used clinically, there is the need to produce advanced functional biomaterials, a new generation of bioinks with suitable cell culture and high shape/print fidelity, to match or exceed the physical, chemical and biological properties of human tissue. With the rapid increase in knowledge associated with biomaterials, cell‐scaffold interactions and the ability to biofunctionalize/decorate bioinks with cell recognition sequences, it is important to keep in mind the 'printability' of these novel materials. In this illustrated review, we define and refine the concept of 'printability' and review seminal and contemporary studies to highlight the current 'state of play' in the field with a focus on bioink composition and concentration, manipulation of nozzle parameters and rheological properties. Abstract : 3D bioprinting has the potential to replicate complex tissue architecture and biomanufacture physiologically relevant multicellular constructs on demand. Advanced functional biomaterials, a new generation of bioinks with suitable biocompatibility and high shape/print fidelity, when combined with the appropriate cell source have the potential to match or exceed the physical, chemical and biological properties of human tissue. Successful clinical translation would revolutionize patient care.